Chapter Introduction: Design and the Changing Educational Landscape - Scharoun, Lisa; Meth, Deanna; Lemos Morais, Renata; Crowther, Philip (Intellect, 2024)
Transdisciplinarity is a term used to describe a process in which disciplines work together to explore problems subordinating disciplinary processes and methods for the common goal of solving the problem or challenge. Along with an overview of the book’s purpose and outline of the chapter structure, this opening chapter summarizes the collective learnings related to context, scope and scale of approaches captured across the book, and the necessary conditions for designing effective transdisciplinary curricula. It defines key terms and provides a framework for understanding teaching and learning in transdisciplinary forms. The book covers four sections: Designing Effective Transdisciplinary Curricula, Transforming Professional Identities through Transdisciplinary Learning,